2012
DOI: 10.1186/cc11649
|View full text |Cite
|
Sign up to set email alerts
|

Relation between proteinuria and acute kidney injury in patients with severe burns

Abstract: IntroductionProteinuria in burn patients is common, and may be associated with acute kidney injury (AKI) and adverse outcomes. We evaluated the incidences, outcomes, characteristics and determinants of proteinuria and its influence on AKI and outcomes in burn patients.MethodsThis retrospective study was carried out in a hospital's burn department. The study population consisted of patients with burn injuries admitted during a five-year period. Positive urine dipstick readings were defined as mild (± or 1+) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Only few studies have examined the significance of de novo proteinuria during AKI. Newonset urinary dipstick proteinuria was associated with severe AKI in critically ill septic patients [60] and increased risk of developing AKI in patients with severe burns [61] . In cardiac surgery patients, high amount of postoperative dipstick proteinuria was associated with the risk of AKI [62] .…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have examined the significance of de novo proteinuria during AKI. Newonset urinary dipstick proteinuria was associated with severe AKI in critically ill septic patients [60] and increased risk of developing AKI in patients with severe burns [61] . In cardiac surgery patients, high amount of postoperative dipstick proteinuria was associated with the risk of AKI [62] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a retrospective cohort of 402 trauma patients who received intravenous contrast, the strongest predictor of contrast-induced AKI was proteinuria measured by dipstick [21]. Similarly, positive urine dipstick readings independently predicted development of AKI in a retrospective cohort of 396 patients with severe burns [22]. Recently, Molnar and colleagues [23] demonstrated that early postoperative albuminuria improved the prediction of AKI in a prospective cohort of 1198 patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In burn patients the proteinuria is often of the mixed type, meaning that it is glomerular and tubular proteinuria. 24,25 However, especially in the first days it is more glomerular proteinuria and later on when acute kidney failure might develop the origin of the proteinuria becomes more tubular. In our patients, no acute kidney failure occurred.…”
Section: Accepted Manuscriptmentioning
confidence: 97%